Anti-Epileptic Drug Toxicity in Children - Imti Choonara (MDPI AG, 2018)
Anti-epileptic drugs (AEDs) have had a major impact on children, improving their quality of life and significantly reducing both morbidity and mortality. They are, however, associated with significant toxicity. Behavioural problems and somnolence are the most frequent adverse drug reactions for many AEDs. Unfortunately, the comparative risk of drug toxicity for different AEDs has been inadequately studied. Drug toxicity is poorly reported in randomised controlled trials. Prospective cohort studies are the best way to study drug toxicity. There have been a few prospective cohort studies of children with epilepsy, but the numbers of children have been small. Systemic reviews of the toxicity of individual AEDs have been helpful in identifying the risk of drug toxicity. Parents of children with epilepsy and the children and young people who are due to receive AED treatment have the right to know the likelihood of them experiencing drug toxicity. Unfortunately, the evidence base on which health professionals can provide such information is limited.